Change and the Persistence of Tradition in India Five Lectures - Park, Richard L. (Michigan Papers On South And Southeast Asia, 2020)
The lectures presented in this volume were given during the summer of 1970 under the sponsorship of the CIC Summer Program on South Asia and the Center for South and Southeast Asian Studies of the University of Michigan. It should be recognized that these essays appear in revised lecture form, and not as fully polished scholarly papers. They carry nevertheless the authority-and no little verve-of experienced scholars concerned with both the traditions and the changes so characteristic of modern India. [v]